Effects of thermal treatment on physical and mechanical properties of Valdieri Marble - NW Italy. (April 2019) - Vagnon, Federico; Colombero, Chiara; Colombo, Fabrizio; Comina, Cesare; Ferrero, Anna Maria; Mandrone, Giuseppe; Vinciguerra, Sergio Carmelo
Abstract: The effect of high temperatures as a degrading factor of rock materials is investigated in this study. Valdieri Marble samples, collected in a quarry in North-western Italian Alps, were subjected to thermal cycles (ranging from 105° to 600 °C) and to subsequent non-destructive and destructive laboratory tests with the aim of evaluating the variation of physical and mechanical properties as a function of temperature variations. Physical and mechanical measurements were complemented with microscopic observations on thin sections. The increase of crack density with temperature and the consequent porosity increases were found to be the main causes of degradation of physical and mechanical properties. In general, density, ultrasonic pulse velocity, wet electrical resistivity, uniaxial compressive strength and Young's moduli decrease as temperature increases. By contrast, peak strain and porosity increase. Correlations between temperature and physical-mechanical properties were proposed and compared to other relationships already established in scientific literature. A damage parameter to quantify the degradation of mechanical properties with temperature is also proposed. Highlights: Laboratory tests on Valdieri marble have been performed to investigate the effect of temperature on physical properties. For the analysed rock, the range of temperature from 200 to 400 °C marks a turning point in the rock behaviour. The porosity can be considered as a significant state parameter related to thermal degradation. An exponential dependence of physical and mechanical parameters with temperature has been observed.